Arbuscular Mycorrhizal Fungal Association in Genetically Modified Drought‐Tolerant Corn. Issue 1 (1st January 2017) - Colombo, Roxana P.; Ibarra, José G.; Bidondo, Laura Fernandez; Silvani, Vanesa A.; Bompadre, María J.; Pergola, Mariana; Lopez, Nancy I.; Godeas, Alicia M.
Abstract : The commercial use of genetically modified (GM) plants has significantly increased worldwide. The interactions between GM plants and arbuscular mycorrhizal (AM) fungi are of considerable importance given the agricultural and ecological role of AM and the lack of knowledge regarding potential effects of drought‐tolerant GM corn ( Zea mays L.) on AM fungal symbiosis. This work studied AM fungal colonization in five corn lines growing under two different irrigation regimes (30 and 100% of soil field capacity [SFC]). Four of the lines were GM corn, and two of these were drought tolerant. The experiment was conducted for 60 d in a growth chamber under constant irrigation, after which mycorrhization, corn biomass, and days to plant senescence (DTS) were evaluated. Arbuscular mycorrhizal fungal species of the order Diversisporales were predominant in the soil inocula. At the end of the experiment, all plants showed AM colonization. Mycorrhization was higher at 30% SFC than at 100% SFC. Within the same corn line, the AM fungi produced more vesicles in plant roots under drought stress. Among treatments, DTS varied significantly, and drought‐tolerant GM corn lines survived longer than the wild‐type corn when maintained at 100% SFC. Corn biomass did not vary among treatments, and no correlations were found between DTS or biomass and mycorrhization. We conclude that overexpression of the Hahb‐4 gene in corn plants under the experimental conditions of this study did not affect AM fungal infectivity and improved the tolerance of the corn to drought stress. Core Ideas: The impact of genetically modified corn on mycorrhization was tested. Mycorrhizal colonization was higher under drought‐stress conditions. Corn biomass and days to senescence were not negatively affected by drought. The transgenic lines tested did not affect the establishment of symbiosis.